Did Adam and Eve really exist? : who they were and why you should care - Collins, C. John, 1954- (Wheaton, Ill. : Crossway, 2011)
"We need a real Adam and Eve if we are to make sense of the Bible and of life," argues C. John Collins. Examining the biblical storyline as the worldview story of the people of God, Collins shows how that story presupposes a real Adam and Eve and how the modern experience of life points to the same conclusion. Applying well-informed critical thinking to common theological and scientific questions, Collins asserts the importance of a real man at the beginning in God's plan for creation, a plan that includes "redemption" for all people since sin entered the world. Did Adam and Eve Really Exist? addresses both biblical and Jewish texts and contains extensive appendices to examine how the material in Genesis relates to similar material from Mesopotamian myths. Collins's detailed analysis of the relevant texts will instill confidence in readers that the traditional Christian story equips them better than any alternatives to engage the life that they actually encounter in the modern world. - Publisher.
The shape of the biblical story -- Particular texts that speak of Adam and Eve -- Human uniqueness and dignity -- Can science help us pinpoint "Adam and Eve"? -- Conclusions -- Appendices.
Includes bibliographical references (p. 171-182) and index.
Keywords: Adam -- (Biblical figure); Eve -- (Biblical figure); Eden; Bible -- Evidences, authority, etc